Desinfecção de efluente sanitário por radiação UV e Gama: efeitos na inativação de ovos de Ascaris SPP - Gloria Suzana Melendez Bastos (2011)
This research aimed to investigate the inactivation of Ascaris spp. eggs during disinfection of domestic sewage by the action of ultraviolet radiation in submerged and emerged lamp demoscale photoreactors, and gamma radiation from 60Co source (bench scale). It was alsoinvestigated the use of different types of Ascaris genus eggs, with and without mammilated membrane as an indicator of disinfection efficiency; and finally evaluated the development of eggs of irradiated Ascaris spp. in the host (murine). The sewage was treated in an anaerobicsystem (UASB reactor) followed by trickling filters (TF) at the Center for Research and Training on Sanitation (CePTS) - UFMG/COPASA. The sewage samples were artificially contaminated with Ascaris spp. eggs and various doses of UV and gamma radiation were tested. After irradiation, sewage samples were analyzed in the laboratory to verify the viability of eggs after incubation in a solution of sulfuric acid 0.1 N, for 28 days, in an incubator at 28°C and daily manual aeration. The inactivation efficiencies were higher than 90% in both UV photoreactors, but the parasitological quality of the effluent did not fit the guidelines of the World Health Organization for the use of treated sewage. As for the gammaradiation, the results indicated the following doses for disinfection of sanitary effluent: 3.5 kGy dose for waste water with lower concentrations of Ascaris spp. eggs and 5 kGy for wastewater with higher concentrations of Ascaris spp. eggs. The results also showed that the mammilated membrane protects the DNA inside the egg against the action of UV and gamma radiation. Finally it was verified by in vivo tests that the use of radiation for wastewater disinfection probably minimizes the risk of host infection (murine model).